2019
DOI: 10.32593/jstmu/vol2.iss2.59
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors associated with acceptance of post-partum intrauterine contraceptive device in a tertiary care hospital

Abstract: Objective: The post-partum intrauterine contraceptive device (PPIUCD) is a highly effective, long acting, reversible, economical and easily accessible family planning method. The aim of the study was to estimate the proportion of pregnant women aware of immediate post-partum intrauterine contraceptive device and to analyze the factors associated with acceptance. Methodology: This is a cross sectional study in which 300 pregnant were selected who were visiting the antenatal clinics and admitted in early l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…This study also showed that mothers having a birth interval of below 24 months increase the odds of accepting immediate PPIUCD by 2.7 when compared with mothers having a birth interval of above 36 months. This association agreed with previous studies conducted in Pakistan [29] and Tanzania [32] that found a greater likelihood of post-partum IUCD acceptance if there had been less than two years since the last birth. Additionally, this finding is supported by a study conducted in Rwanda [4,24] that reports that fear of having an early or unwanted pregnancy was a reason for acceptance of immediate PPFP in 79% of respondents.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study also showed that mothers having a birth interval of below 24 months increase the odds of accepting immediate PPIUCD by 2.7 when compared with mothers having a birth interval of above 36 months. This association agreed with previous studies conducted in Pakistan [29] and Tanzania [32] that found a greater likelihood of post-partum IUCD acceptance if there had been less than two years since the last birth. Additionally, this finding is supported by a study conducted in Rwanda [4,24] that reports that fear of having an early or unwanted pregnancy was a reason for acceptance of immediate PPFP in 79% of respondents.…”
Section: Discussionsupporting
confidence: 92%
“…The possible reason might be that counseling may increase knowledge about PPIUCD and improve the decision-making power of mothers. Supporting evidence is also shown by a study conducted in Pakistan [29] and Rwanda [4], where counseling for mothers during prenatal visits increased the awareness of mothers regarding the PPIUCD. It could also be explained during counseling, when health care providers may clarify misconceptions about PPIUCD and motivate the women to accept PPIUCD immediately after delivery.…”
Section: Discussionmentioning
confidence: 68%
“…This study also showed that mothers having birth interval of below 24 months increase the odds of accepting immediate PPIUCD by 2.7 when compared with mothers having birth interval of above 36 months. This association was agreed with previous studies conducted in Pakistan (29) and Tanzania (32) which indicated that, having less than 2 years of duration since last delivery increases the odds of acceptance of post-partum IUCD. Additionally, this nding is supported by a study conducted in Ruwanda (4,24)that reports, fear of having an early or unwanted pregnancy was a reason for acceptance of immediate PPFP in 79% of respondents.…”
Section: Discussionsupporting
confidence: 92%